RONALDA DWORKINA KONCEPCJA ZASAD PRAWA - Dybowski, Maciej (Wydział Prawa i Administracji UAM, 2001)
Among the greatest achievements of Ronald Dworkin as a law philosopher one usually mentions, not only in the Polish theory of law, the distinguishing of two groups of normative statements: rules and principles with other standards as the premise of making judgments; what is more, it is accepted that in this division the two groups have no common components. The first part of this article is devoted to an analysis of these defining elements of legal principles, suggested by Dworkin himself, while in the other part the author makes an attempt to recreate Dworkin’s conception of legal principles, in their connection with the scholar’s conception of political rights, and in particular the true role legal principles play in the process of application o f law in the view of Dworkin.
RONALD DWORKIN’S CONCEPTION OF LEGAL PRINCIPLES